2017
DOI: 10.3390/ma10070707
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations on the Pull-Out Behavior of Tire Strips Reinforced Sands

Abstract: Waste tires have excellent mechanical performance and have been used as reinforcing material in geotechnical engineering; however, their interface properties are poorly understood. To further our knowledge, this paper examines the pull-out characteristics of waste tire strips in a compacted sand, together with uniaxial and biaxial geogrids also tested under the same conditions. The analysis of the results shows that the interlocking effect and pull-out resistance between the tire strip and the sand is very str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The results also indicate that higher normal stress can extend the critical pull-out displacement corresponding to the peak pull-out force. Overall, although the values for pull-out forces in numerical simulations are quite small as shown in Figure 7(a), these general trends are consistent with the experimental findings reported by Li et al (Li et al,2017) shown in Figure 5 plotted by Li et al (2017) was measured in kN/m and it was normalized by the width of the box for comparison. Some interaction between neighbouring tyre strips may affect the result, hence the pull-out force may not be simply divided by a factor of three, and the exact effect of tyre length will be presented later in this paper.…”
Section: )supporting
confidence: 89%
See 1 more Smart Citation
“…The results also indicate that higher normal stress can extend the critical pull-out displacement corresponding to the peak pull-out force. Overall, although the values for pull-out forces in numerical simulations are quite small as shown in Figure 7(a), these general trends are consistent with the experimental findings reported by Li et al (Li et al,2017) shown in Figure 5 plotted by Li et al (2017) was measured in kN/m and it was normalized by the width of the box for comparison. Some interaction between neighbouring tyre strips may affect the result, hence the pull-out force may not be simply divided by a factor of three, and the exact effect of tyre length will be presented later in this paper.…”
Section: )supporting
confidence: 89%
“…It was concluded that the ultimate pull-out capacity of cell-type waste tyres was about 1.25 times larger than that of geocells. Li et al (2017) found that the pull-out loads mobilised by tyre strips were two times higher than the pull-out loads mobilised by the uniaxial and biaxial geogrids, under the same pull-out testing conditions. Additional recent studies (Li et al, 2016;Li et al, 2020;Li et al, 2021) also revealed a good potential of using larger-size waste tyres to partially or completely replace geogrids or geocells.…”
Section: Introductionmentioning
confidence: 81%
“…In addition, they recommended that pull-out tests be performed at a low normal stress. Li et al 12 conducted a series of pull-out tests to investigate and compare the load‒displacement characteristics of tire belts and uniaxial and biaxial geogrid-reinforced sandy soils under different normal stresses. The damage to the tire belt-reinforced sand was progressive, with the shear strength of each part of the sand depending on that of various other parts of the sand.…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies have been conducted on the shear resistance of reinforced soil and on interactions using mixed soil [ 33 , 34 , 35 ]. Grid-type reinforcement has been used in many studies, but studies on the pullout behavior of geosynthetic strips have been conducted to extend the applicability of geosynthetic strips [ 27 , 28 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%